Effects of high-intensity interval training on physical morphology, cardiopulmonary function, and metabolic indicators in older adults: a systematic review and meta-analysis - Men, Jie; Zhao, Chengrui; Xiang, Chenmin; Zhu, Guoyu; Yu, Zhengyang; Wang, Pengbo; Wu, Simin; Zhang, Yuxi; Li, Yishan; Wang, Liuliu; Gong, Xueyan; Yang, Xiang; et al. (Frontiers in Endocrinology, 2025)
BackgroundDespite the growing attention towards the efficacy of high-intensity interval training (HIIT) on older adult health, a consensus regarding the pleiotropic effects of HIIT in this population is yet to be reached. Previous studies have predominantly focused on specific outcomes or particular groups, lacking comprehensive analysis.ObjectiveWe aimed to conduct a systematic evaluation of the impact of HIIT on body composition, cardiopulmonary function, and metabolic parameters in older adults.MethodsThe databases searched included PubMed, Web of Science, Cochrane Library, Scopus, WanFang, and other relevant sources from the inception of the database until July 2023. Randomized controlled trials (RCTs) on the effects of HIIT on body shape, cardiopulmonary function, and metabolic parameters in the older adult were searched.ResultsA total of 87 RCTs meeting the criteria were included, involving 4,213 older adult people. Meta-analysis results showed that HIIT significantly improved body fat percentage (BF%) [MD: −1.63%, p = 0.005], maximal oxygen uptake (VO2max) [MD: 2.46 mL min−1 kg−1, p < 0.00001], maximal heart rate (HRmax) [MD: 2.83 beats min−1, p = 0.02], and high-density lipoprotein (HDL) levels [MD: 0.04 mmol L−1, p = 0.002]. However, for systolic blood pressure (SBP) [MD: 0.49 mmHg, p = 0.60], resting heart rate (HRrest) [MD: −0.95 BPM −1, p = 0.24], triglycerides (TG) [tendency for MD: −0.02 mmol L−1, p = 0.61], low-density lipoprotein (LDL) [MD: −0.04 mmol L−1, p = 0.27] had no significant effect. Sensitivity analysis found that HIIT significantly improved waist circumference (WC) [MD: −1.89 cm, p = 0.17], diastolic blood pressure (DBP) [MD: −0.63 mmHg, p = 0.23], respiratory exchange rate (RER) [MD: 0.01, p = 0.20], total cholesterol (TC) [MD: 0.10 mmol L−1, p = 0.14], and fasting plasma glucose (FPG) [MD:−0.20 mmol L−1, p = 0.08], but the results lacked robustness. There was no significant improvement in DBP [MD: −0.63 mmHg, p = 0.23] and body mass index (BMI) [MD: −0.36 kg m−2, p = 0.06].ConclusionsHIIT has shown certain potential and advantages in improving the physical health of the older adult, especially in cardiopulmonary function. However, more high-quality studies are needed to confirm the effects of HIIT on the physical health of the older adult in the future. It also provides a reference for the clinical practice and family health management of HIIT in the older adult and the development of HIIT guidelines.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/myprospero, identifier CRD42023460252.